The prevalence rate and the role of the spatial extent of pain in nonspecific chronic back pain: a population-based study in the South-West of Germany - Gerhardt, Andreas; Hartmann, Mechthild; Blumenstiel, Klaus; Tesarz, Jonas; Eich, Wolfgang (Pain medicine, 2014)
To determine the prevalence of chronic back pain in the general population and to establish an evidence-based subclassification system for chronic back pain based on pain extent.Representative population-based survey.South-western Germany.Four-thousand representative residents were contacted. The corrected response rate was 61.8% (N = 2,408). Those suffering from chronic back pain (pain ≥45 days/last 3 months) were invited to a clinical evaluation.Chronic back pain, spatial extent of pain, sociodemographic and clinical variables.Age- and sex-adjusted prevalence rate for chronic back pain was 17.7%. Analyzing pain extent, we found that only 19.6% suffered strictly from chronic local back pain, while the majority indicated additional pain regions. Thus, we developed a subclassification system based on pain extent that consists of four more homogeneous groups (19.6% strict chronic local pain, 42.1% chronic regional pain, 24.3% common chronic widespread pain, 13.9% extreme chronic widespread pain). Interestingly, in this system, increasing pain extent was significantly associated with higher distress, as reflected by sociodemographic (e.g., lower education, lower social class, and higher application rate for disability pension) and clinical variables (e.g., higher pain intensity, more pain medication, more consultations, higher impairment, and lower quality of life).Chronic back pain is prevalent and usually involves additional pain areas outside of the back. This challenges the concept of chronic back pain as a distinct entity. To identify patients who are distressed by chronic back pain, a four-class taxonomy based on pain drawings is both feasible and clinically useful.